2001
DOI: 10.1063/1.1364513
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress toward high performance above the Greenwald density limit in impurity seeded discharges in limiter and divertor tokamaks

Abstract: An overview is given of recent advances toward the realization of high density, high confinement plasmas with radiating mantles in limiter and divertor tokamaks worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…[14,15], instabilities driven by impurities were analyzed, and it was demonstrated that their growth rates are reduced with increasing A i . However, the importance of these instabilities for tokamak confinement has been cast in doubt by the discovery of plasma states where anomalous transport is reduced due to the deliberate seeding of impurities [16]. A positive isotope effect was found also in numerical modeling of collisional drift turbulence [17].…”
mentioning
confidence: 94%
“…[14,15], instabilities driven by impurities were analyzed, and it was demonstrated that their growth rates are reduced with increasing A i . However, the importance of these instabilities for tokamak confinement has been cast in doubt by the discovery of plasma states where anomalous transport is reduced due to the deliberate seeding of impurities [16]. A positive isotope effect was found also in numerical modeling of collisional drift turbulence [17].…”
mentioning
confidence: 94%
“…This is an important issue for future reactors, since, with increasing input power, the heating and the erosion of the first wall become a critical point. It has been found in TEXTOR and subsequently in other devices (Asdex-Upgrade, DIII-D, JT-60U) that in these highly radiative regimes the plasma performance improves when density limits are approached (for an overview of these experiments, see [1] and the references quoted there). Of course the accompanying risk is an increase of the plasma pollution, with large values of effective charge Z eff and of the radiated power density from the plasma centre.…”
Section: Introductionmentioning
confidence: 99%
“…High density (n e /n Gr 0.85), confinement (H 98(y, 2) ≈ 1.0) and β (β N 1.8) were realized simultaneously together with a high radiation level. In low triangularity H-modes in the 'septum' configuration (x-point lying on the dome of the MkII-GB divertor), a peaking of the density profile was observed with argon injection, reminiscent of the observations made in the RI mode on TEXTOR [4]. The present work reports only on high triangularity (δ = 0.44) plasmas with the MkII-SRP divertor configuration, without the septum.…”
Section: Introductionmentioning
confidence: 79%
“…Can impurity be used to control/mitigate ELMs? A summary of the previous JET work on argon seeded H-modes is given in [4][5][6]. The experiments reported in these references were performed with the MkII-GB divertor configuration.…”
Section: Introductionmentioning
confidence: 99%